Justiça 4.0: do juiz-sem-consciência à Diké virtual - Massaro, Rubens Luiz Schmidt Rodrigues (2025)
Artificial intelligence is advancing with relentless force in the most diverse areas of society. There have been decades of exponential technological development of algorithms. Artificial intelligence has overcome historical obstacles and surpassed, in some respects, human capacity. Therefore, following the anthropological movement of cognitive evolution, the assimilation of human tasks to algorithms has become an inevitable reality. In some cases, its incorporation is simpler than in others. To say whether the progress of artificial intelligence has been good or not, from a human point of view, we will depend on the analysis of the question of technology, answering the question of whether it is an instrument for human beings to seek their authentic existence in the world or to train them to live in the mundane. Our work addresses the question of technology from a new theme for law, Justice 4.0, a concept that arises with the partial or total incorporation of artificial intelligence into the judicial system, specifically with the replacement of the human judge. With this change, the application of justice loses an essential element for interaction and motivation, which is consciousness. Consciousness is a human attribute and cannot, at least for now, be imitated or even conceived by artificial intelligence. In this context, Justice 4.0 brings an aspect that was previously unusual in the history of law, which leads to the question of whether it is possible to conduct trials without the use of consciousness. Ultimately, to what extent is a human judge necessary for the application of justice? The relationship between the judging body and the parties to the case will no longer be the same, as robotization will cause linguistic structures and semiotics to be rethought. Concern for ethics is another crucial point when we talk about Justice 4.0. How can we ensure that human values are respected by the judicial body, especially when we are talking about pragmatism and social responsibility? This question becomes even more distressing when faced with a judicial system that is part of a Social Democratic State of Law. Furthermore, the use of an algorithm could also be seen as a form of authoritarianism incompatible with the democratic principle. There is also the practical question of knowing how to implement Justice 4.0. In this context, we divided the study into two axes: the virtual Diké and the judge-without-conscience. At the end of it all, we are faced with a striking problem, which is the impact of Justice 4.0 on our existence, a reflection that is shaped by the constructs of Heidegger's existentialist phenomenology, a philosophical perspective that guides the work